Understanding and addressing the resilience crisis of Europe's farming systems: A synthesis of the findings from the SURE-Farm project - Peter H. Feindt; Miranda P. M. Meuwissen; Alfons Balmann; Robert Finger; Erik Mathijs; Wim Paas; Bárbara Soriano; Alisa Spiegel; Julie Urquhart; Pytrik Reidsma (Resilient and sustainable farming systems in Europe: Exploring diversity and pathways, 2022)
This chapter aims to synthesize key findings from the SURE-Farm project. We first discuss possible amendments to the framework to assess the resilience of farming systems. We then review why many of Europe's farming systems face a formidable and structural resilience crisis. While emphasizing the diversity of resilience capacities, challenges and needs, we formulate cornerstones for possible resilience-enhancing strategies. The chapter concludes with critical reflections and suggestions for resilience-enhancing strategies that comprise the levels of farms, farming systems and enabling environments. We identify limitations of the research and suggest avenues for future research on the resilience of farming systems.
Keywords: 330; resilience-enabling strategies; resilience attributes; adaptation; transformation; Common Agricultural Policy (CAP)